A rapid and sensitive reversed phase‐HPLC method for simultaneous determination of ibuprofen and paracetamol in drug samples and their behaviors in simulated gastric conditions. Issue 3 (6th December 2018) - Borahan, Tülay; Unutkan, Tuğçe; Şahin, Ayşe; Bakırdere, Sezgin
Abstract: Paracetamol is a widely used drug for fever and pain relief. Ibuprofen is a common nonsteroidal anti‐inflammatory drug. In this study, a sensitive and accurate reversed phase high performance liquid chromatography method was developed for the simultaneous determination of ibuprofen and paracetamol. The chromatographic separation was achieved on a Phenomenex C18 (250 mm, 4.6 mm, 5 μm) column. Fifty milli molar phosphate buffer (pH 7.5) and methanol were used as mobile phase in a gradient elution mode. The retention times of paracetamol and ibuprofen were 5.7 and 10.4 min, respectively. The linearity of the developed method was established in the range of 0.25 – 250 mg/L with a correlation coefficient of 0.9998 for both analytes. The limit of detection/quantification values were found to be 0.06/0.19 and 0.08/0.26 mg/L for ibuprofen and paracetamol, respectively. The method was successfully applied in drug samples in the form of tablets and suspensions. The calculated concentrations matched with the claimed values on their prospectuses. The drug samples were studied under simulated gastric conditions to determine the behaviors of the analytes in the human body. The obtained results showed no change in the retention time of the analyte peak shapes throughout the 210 minutes.